CNST is Characteristic of Leukemia Stem Cells and is Associated With Poor Prognosis in AML - Liu, Haoyu; Zhang, Xu; Zhao, Ziyan; Zhu, Hongying; Li, Danyang; Yang, Yang; Zhao, Wenbo; Zhang, Fei; Wang, Yuefeng; Zhu, Lina; Ding, Zewen; Li, Xiangzhi (Frontiers in Pharmacology, 2022)
Consortin (CNST) is a protein located on the trans-Golgi network that can target transmembrane proteins to the plasma membrane. Although CNST was discovered more than 10 years ago, there are still not enough studies on its function. During our search for possible new acute myeloid leukemia (AML) markers, we found that CNST was overexpressed in almost all patients with AML. By analyzing profiling data from public databases, we found that CNST expression inversely correlated with overall survival among AML patients. There was a great variation in CNST expression among different subtypes of AML, and the expression was the highest in the t(8,21) subtype, which was probably due to the direct regulation of CNST transcription by RUNX1-RUNX1T1. In addition, we analyzed the expression of CNST in different cells of the hematopoietic system. We found that CNST was associated with the low differentiation degrees of hematopoietic cells and had the highest expression level in leukemia stem cells (LSCs). Finally, we analyzed the CNST-related gene network and found that the genes negatively correlated with CNST are involved in various immune-related pathways, which indicates that CNST is likely related to immune evasion, LSC niche retention, and assembly of stress granules (SGs). In conclusion, our study suggests that CNST has the potential to be a diagnostic and prognostic biomarker for AML.